Preparation method and application of all-solid-state lithium-sulfur battery composite solid electrolyte
By introducing MOF-5 particles with an ordered porous structure into a PEO-based electrolyte, a composite electrolyte CPE-MOF was prepared. This solved the problems of polysulfide shuttle effect and reaction kinetics in all-solid-state lithium-sulfur batteries, achieving high ionic conductivity and stable electrochemical performance, and improving the battery's discharge specific capacity and cycle stability.
Patent Information
- Application Number
- CN202511168474.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-11-18
AI Technical Summary
All-solid-state lithium-sulfur batteries suffer from the shuttle effect of polysulfides and slow reaction kinetics, resulting in poor battery cycle stability and low ionic conductivity. Existing PEO-based electrolytes also exhibit poor stability and low ionic conductivity in their lithium anodes.
By using ordered porous MOF-5 particles as inorganic fillers, combined with PEO substrate and lithium salt, a composite electrolyte CPE-MOF was prepared. This electrolyte captures polysulfides through physical adsorption and chemical bonding, suppresses the shuttle effect, and improves ionic conductivity and electrochemical stability.
It significantly improves the ionic conductivity and electrochemical stability of all-solid-state lithium-sulfur batteries, enhances the battery's discharge specific capacity and cycle performance, and exhibits good rate performance and stable cycle performance.
Smart Images

Figure CN120978175A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of all-solid-state lithium-sulfur batteries, and particularly relates to a preparation method and application of a composite solid electrolyte of an all-solid-state lithium-sulfur battery. BACKGROUND
[0002] The all-solid-state lithium-sulfur battery system has great potential in the next generation of energy storage technology due to its significant theoretical capacity advantage, high specific energy, and abundant sulfur resources. However, this system still faces two major challenges in practical applications: the shuttle effect of polysulfides and the slow reaction kinetics, which severely limit its commercialization process. Among various solid-state electrolytes, polyethylene oxide (PEO)-based polymer electrolytes are of great interest due to their excellent safety performance and lower interfacial impedance. However, this type of electrolyte still has defects such as poor lithium anode stability and low ionic conductivity. In addition, the shuttle effect of polysulfides still exists in the PEO-based electrolyte solid-state lithium-sulfur battery system, resulting in poor battery cycle stability. Studies have shown that by introducing functional fillers or organic plasticizers into the PEO matrix, the crystallinity can be effectively reduced, thereby improving the ionic conductivity. Among them, metal-organic framework (MOF) materials are ideal filler choices due to their unique structural and performance advantages. MOF is a porous crystalline material composed of metal ion clusters and organic ligands, with adjustable pore size structure and surface chemical properties. This material not only can selectively separate different molecules, but also can act as a lithium ion transmission channel, while reducing the crystallinity of PEO by disrupting the ordered arrangement of polymer chains, thereby significantly improving the ionic conductivity of the composite electrolyte. SUMMARY
[0003] To overcome the deficiencies of the prior art, the purpose of the present application is to provide a preparation method of a high-ionic-conductivity composite solid electrolyte for an all-solid-state lithium-sulfur battery. The present application uses MOF-5 particles with ordered porous structure as inorganic fillers to prepare CPE-MOF composite electrolyte with high ionic conductivity. MOF-5 is a three-dimensional structural material with Zn 2+ as the metal center and terephthalic acid (H2BDC) as the organic ligand. Its surface contains a large number of Lewis acid sites, which can interact with the PEO matrix and lithium salt, thereby significantly improving the ionic conductivity and electrochemical stability of the electrolyte. In addition, the porous structure of MOF-5 can effectively capture polysulfides through physical adsorption and chemical bonding, inhibit the shuttle effect, and improve the stability of the battery.
[0004] The technical scheme adopted by the present application to solve the above technical problems is:
[0005] A preparation method of a composite solid electrolyte of an all-solid-state lithium-sulfur battery, taking polyethylene oxide (PEO) as a base, adding inorganic fillers to prepare a composite polymer electrolyte film (CPE), and adding ordered porous structure organic metal framework MOF-5 particles on the basis of the electrolyte film to prepare a composite solid electrolyte CPE-MOF, comprising the following steps:
[0006] MOF-5 particle preparation:
[0007] S1. Dissolve polyvinylpyrrolidone (PVP), terephthalic acid (TPA) and triethylamine (TEA) in a solvent, stir until the reagents are uniformly mixed to obtain solution A;
[0008] S2. Dissolve Zn(NO3)2·6H2O in DMF to obtain solution B;
[0009] S3. Add solution B to solution A, and perform reaction under oil bath and stirring conditions, cool and precipitate the obtained white solution, centrifuge and wash, and vacuum dry to obtain white MOF-5 powder;
[0010] Composite solid electrolyte CPE-MOF preparation:
[0011] A1. Add inorganic materials, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), PEO and MOF-5 to acetonitrile, and stir at constant temperature until a particle-free viscous liquid is obtained;
[0012] A2. Pour the liquid into a mold, and after standing and natural air drying, obtain an electrolyte film CPE-MOF with uniform thickness;
[0013] The preparation of the composite solid electrolyte is performed in an argon atmosphere.
[0014] In S1, the ratio of PVP, TPA and TEA is 6g:1.4g:300μL; the solvent is a solution obtained by mixing DMF and anhydrous ethanol in a volume ratio of 60:27; and the stirring speed is 750rpm;
[0015] In S2, the mass-volume ratio of Zn(NO3)2·6H2O to DMF is Zn(NO3)2·6H2O:DMF=267g:900mL;
[0016] In S3, the oil bath temperature is 120℃, the stirring speed is 500rpm-650rpm, the reaction time is 2h-4h; the centrifugal washing process is to wash at least 3 times with methanol to remove impurities; and the vacuum drying conditions are 60℃ vacuum drying for 12h-16h.
[0017] The MOF-5 is prepared by using Zn 2+A three-dimensional structure material with a metal center and terephthalic acid (TPA) as an organic ligand;
[0018] In A1, the inorganic filler comprises Li 1.5 Al 0.5 Ge 1.5 (PO4)3 (LAGP) and Li 10 GeP2S 12 (LGPS); the LAGP is added in an amount of 5wt%-15wt%, the LGPS is added in an amount of 5wt%-15wt%, the mass ratio of LiTFSI to PEO is 7:192, and the MOF-5 is added in an appropriate amount (1wt%-5wt%);
[0019] The constant temperature stirring condition is stirring at a speed of 600rpm-650rpm at 60℃ for at least 12h;
[0020] In A2, the standing time is at least 12h.
[0021] Application of the solid-state electrolyte in a full-solid-state lithium-sulfur battery composite.
[0022] Compared with the prior art, the present application has the following technical effects:
[0023] 1、The MOF-5 material prepared by the oil bath method in the present application shows a typical cubic structure and has a micron-level size. The synthesis has good repeatability and controllability, and lays a solid foundation for the subsequent research and application of material performance.
[0024] 2、The composite solid-state electrolyte CPE-MOF prepared in the present application is applied to a full-solid-state lithium-sulfur battery. The addition of MOF-5 can make the crystallinity of the PEO base decrease, the amorphous region increase, and further promote the dissociation of lithium salt. At the same time, the addition of MOF-5 can reduce the melting temperature of the electrolyte, break the regular arrangement of the PEO chain segment, and thus effectively improve the ionic conductivity of the electrolyte.
[0025] 3、The MOF-5 material synthesized in the present application contains a large number of Lewis acid sites, which can coordinate with the PEO base, thereby improving the oxidation voltage and ion migration number of the composite electrolyte. In addition, the CPE-MOF composite electrolyte also shows excellent cycle performance, because the Lewis acid sites of MOF-5 have the ability of chemical adsorption to polysulfides, and the MOF-5 inorganic filler has a porous structure, and polysulfides can be anchored in the pores, thereby inhibiting the shuttle of polysulfides.
[0026] 4. The composite solid electrolyte is prepared by simple casting method, and each component such as polymer, lithium salt and inorganic filler is mixed and stirred in liquid state, so that the components can be uniformly dispersed at molecular or nanometer level, which is important for obtaining uniform ion transmission channel and stable electrochemical performance.
[0027] 5. The lithium-sulfur battery using the composite electrolyte synthesized by the application can exhibit high discharge specific capacity, stable cycle performance and good rate performance. BRIEF DESCRIPTION OF DRAWINGS
[0028] Figure 1 The process flow chart of the preparation method and application of the composite solid electrolyte of the full solid-state lithium-sulfur battery provided by the application is shown in the figure.
[0029] Figure 2 The SEM photos of MOF-5 and electrolyte film CPE-1M prepared in Example 1 and electrolyte film CPE prepared in Example 6 of the application are shown in the figure; wherein, (a) and (b) are MOF-5, (c) is CPE, and (d) is CPE-1M.
[0030] Figure 3 The rate performance graphs of the full solid-state lithium-sulfur batteries prepared in Examples 1-3 and Example 6 of the application are shown in the figure; wherein, (a) is 1 # battery, (b) is 2 # battery, (c) is 3 # battery, (d) is 6 # battery.
[0031] Figure 4 The cycle performance graphs (0.5C) of the full solid-state lithium-sulfur batteries prepared in Examples 1-3 and Example 6 of the application are shown in the figure; wherein, (a) is 1 # battery, (b) is 2 # battery, (c) is 3 # battery, (d) is 6 # battery.
[0032] Figure 5 The ion conductivities of the electrolytes obtained in Examples 1-3 and Example 6 of the application at different temperatures are shown in the figure; wherein, (a) is CPE-1M, (b) is CPE-3M, (c) is CPE-5M, and (d) is CPE.
[0033] Figure 6 The ion transference numbers of the electrolytes obtained in Examples 1-3 and Example 6 of the application are shown in the figure; wherein, (a) is CPE-1M, (b) is CPE-3M, (c) is CPE-5M, and (d) is CPE. DETAILED DESCRIPTION
[0034] The present application will be described in detail below in conjunction with the accompanying drawings and specific embodiments, but the present application is not limited to the following embodiments.
[0035] The present application provides a preparation method and application of a composite solid-state electrolyte of a full-solid-state lithium-sulfur battery, and a process flow thereof is shown in Figure 1 The composite polymer electrolyte film (CPE) is prepared by adding inorganic fillers to polyethylene oxide (PEO) as a base in an argon atmosphere. On the basis of the electrolyte film, ordered porous structure organic metal framework MOF-5 particles are added to prepare a composite solid-state electrolyte CPE-MOF. The prepared solid-state electrolyte film CPE-MOF can be used for a full-solid-state lithium-sulfur battery. The preparation method of the composite solid-state electrolyte CPE-MOF includes the following steps:
[0036] Preparation of MOF-5 particles:
[0037] S1. Polyvinylpyrrolidone (PVP), terephthalic acid (TPA), and triethylamine (TEA) are dissolved in a solution obtained by mixing DMF and anhydrous ethanol in a volume ratio of 60:27 in a ratio of 6g:1.4g:300μL. After stirring at a speed of 750rpm until the reagents are uniformly mixed, solution A is obtained;
[0038] S2. Zn(NO3)2·6H2O is dissolved in DMF in a ratio of Zn(NO3)2·6H2O:DMF=267g:900mL to obtain solution B;
[0039] S3. Solution B is added to solution A, and the reaction is carried out at 120℃ oil bath and a stirring speed of 500rpm-650rpm for 2h-4h. The obtained white solution is cooled and precipitated, centrifuged, washed with methanol at least 3 times to remove impurities, and vacuum dried at 60℃ for 12h-16h to obtain white powder MOF-5. MOF-5 is a three-dimensional structure material with Zn 2+ as a metal center and terephthalic acid (TPA) as an organic ligand.
[0040] Preparation of composite solid-state electrolyte CPE-MOF:
[0041] A1. Inorganic materials, lithium bis-trifluoromethanesulfonimide (LiTFSI), PEO, and MOF-5 are added to acetonitrile, and stirred at a speed of 600rpm-650rpm at 60℃ for at least 12h to obtain a granule-free viscous liquid; the inorganic fillers include Li 1.5 Al 0.5 Ge 1.5 (PO4)3 (LAGP), and Li 10 GeP2S 12(LGPS); The addition amount of LAGP is 5wt%-15wt%, the addition amount of LGPS is 5wt%-15wt%, the mass ratio of LiTFSI to PEO is 7:192, and the addition amount of MOF-5 is 1wt%-5wt%.
[0042] A2. Pour the liquid into a mold, let it stand for at least 12 hours, and then air dry to obtain a uniformly thick electrolyte film CPE-MOF.
[0043] Example 1:
[0044] MOF-5 particle preparation:
[0045] (1) Dissolve 6g of polyvinylpyridinium (PVP), 1.4g of terephthalic acid (TPA) and 300μL of triethylamine (TEA) in 240mL of DMF and 108mL of anhydrous ethanol, and stir at 750rpm to prepare solution A.
[0046] (2) Weigh 5.34g of Zn(NO3)2·6H2O and dissolve it in 18mL of DMF to obtain solution B.
[0047] (3) Add solution B to solution A, and then stir at 500 rpm for 2 hours in an oil bath at 120°C to obtain a milky white solution. After cooling and precipitation, wash three times with methanol to remove other impurities. After drying in a vacuum drying oven at 60°C for 12 hours, obtain white powdered MOF-5 (e.g. Figure 2 As shown in (a) and (b) in the middle.
[0048] A simple casting method is used to prepare composite solid electrolytes:
[0049] (1) In an argon glove box, weigh 0.768g PEO, 0.28g LiTFSI, 0.1048g LAGP, 0.1048g LGPS and 1% MOF-5 and add them to a glass bottle, then add 16mL of acetonitrile. Stir at 600rpm for 12 hours at 60℃ until it becomes a smooth, viscous liquid without particles.
[0050] (2) Pour the mixed solution into a polytetrafluoroethylene mold, and let it stand in a glove box for 12 hours to air dry naturally to obtain a uniformly thick electrolyte film CPE-1M (e.g. Figure 2 (d) is shown.
[0051] Using CPE-1M as the solid electrolyte membrane, lithium metal sheet as the negative electrode, and S@KB electrode sheet as the positive electrode, a CR2032 coin-type solid lithium-ion battery was assembled in an argon-filled glove box, denoted as 1. # Battery.
[0052] The preparation of S@KB composite positive electrode material adopts a two-step calcination method. First, 365 mg of S powder and 150 mg of Ketjen black (KB) are accurately weighed and placed in a mortar for grinding for 1 hour. Then, the mixture is transferred to a cleaned and dried glass bottle and sealed with high-temperature aluminum tape. The sample is placed in a tube furnace under an argon atmosphere and heated at a rate of 2 ℃·min -1 -1 to 155 ℃ and kept for 5 hours, and then naturally cooled to room temperature. After cooling, the sample is ground again for 30 minutes, resealed and placed in a tube furnace for the second calcination. It is still heated at a rate of 2 ℃·min -1 -1 to 200 ℃ under an argon atmosphere, kept for 2 hours and then naturally cooled. Finally, the sample is taken out and ground for 30 minutes to obtain the S@KB composite positive electrode material. The binder is prepared in an inert atmosphere glove box. First, 11.4 g of DMF solvent is added to a glass bottle, followed by the addition of 0.44 g of PEO and 0.16 g of LiTFSI. The mixture is placed on a heated stirrer and stirred at 600 rpm for 12 hours at 60 ℃. After stirring, the solution is left to stand at room temperature for 30 minutes, and a uniform binder solution is finally obtained. S@KB and the binder are weighed according to the solid content ratio of active material to binder of 7:3 and placed in a small beaker, and an appropriate amount of DMF solvent is added. Stir continuously at 34 ℃ for 10 hours until a uniform and particle-free thick slurry is formed. Then, the slurry is evenly coated on the surface of the carbon-coated aluminum foil and placed in a vacuum drying oven at 60 ℃ for 12 hours. Finally, the dried electrode is cut into a circular electrode sheet for subsequent battery assembly.
[0053] 1 # The battery is charged and discharged at different rates in the potential range of 1.5 V-2.8 V at 60 ℃. When the 1 # battery is charged and discharged at 0.3 C (1 C = 1600 mAh·g -1 ), the discharge specific capacity is 1246.1 mAh·g -1 , and at rates of 0.5 C, 1 C, 2 C and 5 C, the discharge specific capacities are 1089.6 mAh·g -1 , 759.3 mAh·g -1 , 472.9 mAh·g -1 and 266.6 mAh·g -1 , respectively. When the rate returns to 0.3 C, the discharge specific capacity is still 1233.4 mAh·g -1 , almost the same as the initial value, confirming the good reversibility of the 1 # battery (as Figure 3(as shown in (a)). During charge-discharge cycle testing at 0.5C, due to incomplete reaction in the first cycle, statistics were collected starting from the second cycle. The initial discharge specific capacity of the CPE-1M electrolyte reached 1138.1 mAh·g. -1 It exhibited good cycle stability and high coulombic efficiency, and the discharge specific capacity remained at 1067.8 mAh·g after 100 cycles. -1 It has an ultra-high capacity retention rate of 93.8% (e.g. Figure 4 (as shown in (a)). The ionic conductivity of this electrolyte at 60 °C is 1.45 × 10⁻⁶. -3 S·cm -1 (like Figure 5 (a) shows that the ion transport number is 0.215 (as shown in the figure). Figure 6 (a) is shown.
[0054] Example 2:
[0055] MOF-5 particle preparation:
[0056] (1) Dissolve 6g of polyvinylpyridinium (PVP), 1.4g of terephthalic acid (TPA) and 300μL of triethylamine (TEA) in 240mL of DMF and 108mL of anhydrous ethanol, and stir at 750rpm to prepare solution A.
[0057] (2) Weigh 5.34g of Zn(NO3)2·6H2O and dissolve it in 18mL of DMF to obtain solution B.
[0058] (3) Add solution B to solution A, and then stir at 500 rpm for 2 hours in an oil bath at 120°C to obtain a milky white solution. After cooling and precipitation, wash three times with methanol to remove other impurities. After drying in a vacuum drying oven at 60°C for 12 hours, a white powdery MOF-5 is obtained.
[0059] A simple casting method is used to prepare composite solid electrolytes:
[0060] (1) In an argon glove box, weigh 0.768g PEO, 0.28g LiTFSI, 0.1048g LAGP, 0.1048g LGPS and 3% MOF-5 and add them to a glass bottle, then add 16mL of acetonitrile. Stir at 600rpm for 12 hours at 60℃ until it becomes a smooth, viscous liquid without particles.
[0061] (2) Pour the mixed solution into a polytetrafluoroethylene mold and let it stand in a glove box for 12 hours to air dry naturally to obtain a uniformly thick electrolyte film CPE-3M.
[0062] Using CPE-3M as the solid electrolyte membrane, lithium metal sheet as the negative electrode, and S@KB electrode sheet as the positive electrode, a CR2032 coin-type solid lithium-ion battery was assembled in an argon-filled glove box, denoted as 2. # Battery.
[0063] The S@KB composite cathode material was prepared using a two-step calcination method. First, 365 mg of sulfur powder and 150 mg of Ketjen Black (KB) were accurately weighed and placed in a mortar, then ground thoroughly for 1 hour. Next, the mixture was transferred to a clean, dried glass bottle and sealed with high-temperature aluminum tape. Under argon protection, the sample was placed in a tube furnace at 2 °C / min. -1 The temperature was increased to 155°C at a rate of [missing information] and held for 5 hours, then allowed to cool naturally to room temperature. After cooling, the sample was ground again for 30 minutes, resealed, and placed in a tube furnace for a second calcination. The calcination was still carried out under an argon atmosphere at a rate of 2°C / min. -1 The temperature was raised to 200℃ at a constant rate, held for 2 hours, and then allowed to cool naturally. Finally, the sample was removed and ground for 30 minutes to obtain the S@KB composite cathode material. A binder was prepared in a glove box filled with an inert atmosphere. First, 11.4 g of DMF solvent was added to a glass bottle, followed by 0.44 g of PEO and 0.16 g of LiTFSI. The mixture was placed on a heated stirrer and stirred continuously at 600 rpm for 12 hours at 60℃. After stirring, the solution was allowed to stand at room temperature for 30 minutes to obtain a homogeneous binder solution. S@KB and binder were weighed according to a solid content ratio of 7:3 (active material to binder) and placed in a small beaker, with an appropriate amount of DMF solvent added. The mixture was stirred continuously at 34℃ for 10 hours until a homogeneous, particle-free viscous slurry was formed. The slurry was then evenly coated onto the surface of carbon-coated aluminum foil and placed in a vacuum drying oven at 60℃ for 12 hours. Finally, the dried electrode was cut into circular electrode sheets for subsequent battery assembly.
[0064] 2 # The battery was charged and discharged at 60℃ within a potential range of 1.5V-2.8V at different rates. When 2 # The battery exhibits a discharge specific capacity of 1025.3 mAh·g at discharge rates of 0.3C, 0.5C, 1C, 2C, and 5C. -1 866.4mAh·g -1 579.8mAh·g -1 351.2 mAh·g -1 and 186.77mAh·g -1 When the discharge rate returns to 0.3C, the discharge specific capacity remains at 1088.3 mAh·g. -1 It is almost identical to the initial value, confirming that 2 # The battery has good reversibility (e.g.)Figure 3 (b) shown). In the charge-discharge cycle test at 0.5C rate, due to incomplete reaction in the first circle, from the second circle, the initial discharge specific capacity of CPE-3M electrolyte reached 935.2 mAh·g -1 , which showed good cycle stability and high coulomb efficiency, and the discharge specific capacity remained at 953.63 mAh·g -1 after 100 cycles, and it could be found that the capacity change trend was gradually slow rise and then kept stable (as shown in Figure 4 (b)). The ionic conductivity of the electrolyte at 60°C was 9.27 x 10 -4 S·cm -1 (as shown in Figure 5 (b)), and the ion transference number was 0.141 (as shown in Figure 6 (b)).
[0065] Example 3:
[0066] Preparation of MOF-5 particles:
[0067] (1) 6 g of polyvinylpyrrolidone (PVP), 1.4 g of terephthalic acid (TPA) and 300 μL of triethylamine (TEA) were dissolved in 240 mL of DMF and 108 mL of anhydrous ethanol, and stirred at 750 rpm to mix them thoroughly to prepare solution A.
[0068] (2) 5.34 g of Zn(NO3)2·6H2O was weighed and dissolved in 18 mL of DMF to obtain solution B.
[0069] (3) Solution B was added to solution A, and then stirred at 500 rpm in an oil bath at 120°C for 2 hours to obtain a milky white solution. After cooling and precipitation, the other impurities were washed off by centrifugation with methanol three times on a centrifuge. After drying in a vacuum drying oven at 60°C for 12 hours, white powdery MOF-5 was obtained.
[0070] The composite solid-state electrolyte was prepared by a simple casting method:
[0071] (1) In an argon glove box, 0.768 g of PEO, 0.28 g of LiTFSI, 0.1048 g of LAGP, 0.1048 g of LGPS and 5% of MOF-5 were weighed into a glass bottle, and then 16 mL of acetonitrile was added. Stir at 600 rpm for 12 hours at 60°C until the mixture is uniformly stirred into a viscous liquid without particles.
[0072] (2) Pour the mixed solution into a polytetrafluoroethylene mold, and let it dry naturally in the glove box for 12 hours to obtain an electrolyte thin film CPE-5M with uniform thickness.
[0073] The obtained product was used as a solid electrolyte film, a piece of lithium metal as a negative electrode, and the S@KB electrode sheet as a positive electrode to assemble a CR2032 type button solid-state lithium ion battery in an argon-filled glove box, denoted as 3 # battery.
[0074] The preparation of the S@KB composite positive electrode material adopted a two-step calcination method. First, 365 mg of S powder and 150 mg of KB were accurately weighed and placed in a mortar for grinding for 1 hour. Then, the mixture was transferred to a cleaned and dried glass bottle and sealed with high-temperature aluminum tape. The sample was placed in a tube furnace under argon protection and heated to 155°C at a rate of 2°C·min -1 -1, and kept for 5 hours, and then naturally cooled to room temperature. After cooling, the sample was ground again for 30 minutes, resealed and placed in the tube furnace for the second calcination. It was still heated to 200°C at a rate of 2°C·min -1 -1 under argon atmosphere, and kept for 2 hours and then naturally cooled. Finally, the sample was taken out and ground for 30 minutes to obtain the S@KB composite positive electrode material. The binder was prepared in an inert atmosphere glove box. First, 11.4 g of DMF solvent was added to a glass bottle, followed by the addition of 0.44 g of PEO and 0.16 g of LiTFSI. The mixture was placed on a heated stirrer and stirred at 600 rpm for 12 hours at 60°C. After stirring, the solution was left to stand at room temperature for 30 minutes, and finally a uniform binder solution was obtained. S@KB and binder were weighed according to the solid content ratio of 7:3 and placed in a small beaker, and an appropriate amount of DMF solvent was added. Stir continuously at 34°C for 10 hours until a uniform and particle-free thick slurry is formed. Then, the slurry was evenly coated on the surface of the carbon-coated aluminum foil and placed in a vacuum drying oven at 60°C for 12 hours. Finally, the dried electrode was cut into a circular electrode sheet for subsequent battery assembly.
[0075] The 3 # battery was charged and discharged at different rates in the potential range of 1.5V-2.8V at 60°C. When the 3 # battery was discharged at rates of 0.3C, 0.5C, 1C, 2C and 5C, the specific capacity was 1140.2mAh·g -1 , 889.7mAh·g -1 , 535.2mAh·g -1 , 316.6mAh·g -1 and 171.1mAh·g -1 , and when the rate returned to 0.3C, the specific capacity was still 1092.9mAh·g -1 , almost the same as the initial value, confirming that the 3 #Good reversibility of the battery (e.g. Figure 3 The initial discharge specific capacity of CPE-5M electrolyte reached 875.1 mAh·g -1 , showing good cycle stability and high coulombic efficiency, and the discharge specific capacity remained at 711.8 mAh·g -1 after 100 cycles, with a capacity retention rate of 81.3% (as shown in (c)). Figure 4 The ionic conductivity of the electrolyte at 60°C was 7.66 x 10 -4 S·cm -1 (as shown in (c)), and the ion transference number was 0.125 (as shown in (c)). Figure 5 Figure 6
[0076] Example 4:
[0077] Preparation of MOF-5 particles:
[0078] (1) 6 g of polyvinylpyrrolidone (PVP), 1.4 g of terephthalic acid (TPA), and 300 μL of triethylamine (TEA) were dissolved in 240 mL of DMF and 108 mL of anhydrous ethanol, and stirred at 750 rpm to mix thoroughly to prepare solution A.
[0079] (2) 5.34 g of Zn(NO3)2·6H2O was dissolved in 18 mL of DMF to obtain solution B.
[0080] (3) Solution B was added to solution A, and then stirred at 500 rpm in an oil bath at 120°C for 2 hours to obtain a milky white solution. After cooling and precipitation, the solution was centrifuged with methanol three times to wash away other impurities. After drying in a vacuum drying oven at 60°C for 12 hours, white powder MOF-5 was obtained.
[0081] Preparation of composite solid-state electrolyte using a simple casting method:
[0082] (1) In an argon glove box, 0.768 g of PEO, 0.28 g of LiTFSI, 0.0524 g of LAGP, 0.0524 g of LGPS, and 1% of MOF-5 were weighed into a glass bottle, and then 15 mL of acetonitrile was added. Stirring was carried out at 600 rpm for 12 hours at 60°C until the solution was uniformly viscous and free of particles.
[0083] (2) The mixed solution was poured into a polytetrafluoroethylene mold, and after standing in the glove box for 12 hours to dry naturally, a uniform thickness electrolyte film CPE-1M-1 was obtained.
[0084] Using CPE-1M-1 as the solid electrolyte membrane, lithium metal sheet as the negative electrode, and S@KB electrode sheet as the positive electrode, a CR2032 coin-type solid lithium-ion battery was assembled in an argon-filled glove box, denoted as 4. # Battery. 4 # The battery was charged and discharged at 60°C within a potential range of 1.5V-2.8V at different rates.
[0085] The S@KB composite cathode material was prepared using a two-step calcination method. First, 365 mg of sulfur powder and 150 mg of Ketjen Black (KB) were accurately weighed and placed in a mortar, then ground thoroughly for 1 hour. Next, the mixture was transferred to a clean, dried glass bottle and sealed with high-temperature aluminum tape. Under argon protection, the sample was placed in a tube furnace at 2 °C / min. -1 The temperature was increased to 155°C at a rate of [missing information] and held for 5 hours, then allowed to cool naturally to room temperature. After cooling, the sample was ground again for 30 minutes, resealed, and placed in a tube furnace for a second calcination. The calcination was still carried out under an argon atmosphere at a rate of 2°C / min. -1 The temperature was raised to 200℃ at a constant rate, held for 2 hours, and then allowed to cool naturally. Finally, the sample was removed and ground for 30 minutes to obtain the S@KB composite cathode material. A binder was prepared in a glove box filled with an inert atmosphere. First, 11.4 g of DMF solvent was added to a glass bottle, followed by 0.44 g of PEO and 0.16 g of LiTFSI. The mixture was placed on a heated stirrer and stirred continuously at 600 rpm for 12 hours at 60℃. After stirring, the solution was allowed to stand at room temperature for 30 minutes to obtain a homogeneous binder solution. S@KB and binder were weighed according to a solid content ratio of 7:3 (active material to binder) and placed in a small beaker, with an appropriate amount of DMF solvent added. The mixture was stirred continuously at 34℃ for 10 hours until a homogeneous, particle-free viscous slurry was formed. The slurry was then evenly coated onto the surface of carbon-coated aluminum foil and placed in a vacuum drying oven at 60℃ for 12 hours. Finally, the dried electrode was cut into circular electrode sheets for subsequent battery assembly.
[0086] Example 5:
[0087] MOF-5 particle preparation:
[0088] (1) Dissolve 6g of polyvinylpyridinium (PVP), 1.4g of terephthalic acid (TPA) and 300μL of triethylamine (TEA) in 240mL of DMF and 108mL of anhydrous ethanol, and stir at 750rpm to prepare solution A.
[0089] (2) Weigh 5.34g of Zn(NO3)2·6H2O and dissolve it in 18mL of DMF to obtain solution B.
[0090] (3) Add B solution to A solution, then stir at 500 rpm in an oil bath at 120 °C for 2 hours to obtain a milky white solution. After the precipitate is cooled, wash it with methanol three times on a centrifuge to remove other impurities. After drying in a vacuum drying oven at 60 °C for 12 hours, a white powder of MOF-5 is obtained.
[0091] A simple casting method was used to prepare the composite solid-state electrolyte:
[0092] (1) In an argon glove box, weigh 0.768 g of PEO, 0.28 g of LiTFSI, 0.1572 g of LAGP, 0.1572 g of LGPS, and 1% of MOF-5 into a glass bottle, then add 16 mL of acetonitrile. Stir at 600 rpm at 60 °C for 12 hours until the mixture is uniformly stirred into a granular viscous liquid.
[0093] (2) Pour the mixed solution into a polytetrafluoroethylene mold, and after natural air drying for 12 hours in the glove box, a uniform thickness electrolyte film CPE-1M-2 is obtained.
[0094] Using CPE-1M-2 as the solid-state electrolyte film, a lithium metal sheet as the negative electrode, and an S@KB electrode sheet as the positive electrode, a CR2032 type button solid-state lithium ion battery was assembled in an argon-filled glove box, 5 # Battery. The 5 # Battery was cycled at different rates at 60 °C in the potential range of 1.5 V-2.8 V.
[0095] The preparation of the S@KB composite positive electrode material used a two-step calcination method. First, accurately weigh 365 mg of S powder and 150 mg of KB, and place the two raw materials in a mortar and grind for 1 hour. Then, transfer the mixture to a cleaned and dried glass bottle, and seal it with high-temperature aluminum tape. Place the sample in a tube furnace under argon protection, and heat it to 155 °C at a rate of 2 °C·min -1 -1, and keep it at this temperature for 5 hours, then naturally cool to room temperature. After cooling, the sample is ground again for 30 minutes, resealed and placed in the tube furnace for the second calcination. Again, under an argon atmosphere, heat it to 155 °C at a rate of 2 °C·min -1The temperature was raised to 200℃ at a constant rate, held for 2 hours, and then allowed to cool naturally. Finally, the sample was removed and ground for 30 minutes to obtain the S@KB composite cathode material. A binder was prepared in a glove box filled with an inert atmosphere. First, 11.4 g of DMF solvent was added to a glass bottle, followed by 0.44 g of PEO and 0.16 g of LiTFSI. The mixture was placed on a heated stirrer and stirred continuously at 600 rpm for 12 hours at 60℃. After stirring, the solution was allowed to stand at room temperature for 30 minutes to obtain a homogeneous binder solution. S@KB and binder were weighed according to a solid content ratio of 7:3 (active material to binder) and placed in a small beaker, with an appropriate amount of DMF solvent added. The mixture was stirred continuously at 34℃ for 10 hours until a homogeneous, particle-free viscous slurry was formed. The slurry was then evenly coated onto the surface of carbon-coated aluminum foil and placed in a vacuum drying oven at 60℃ for 12 hours. Finally, the dried electrode was cut into circular electrode sheets for subsequent battery assembly.
[0096] Example 6:
[0097] A simple casting method is used to prepare composite solid electrolytes:
[0098] (1) In an argon glove box, weigh 0.768g PEO, 0.28g LiTFSI, 0.1048g LAGP, and 0.1048g LGPS and add them to a glass bottle, then add 14mL of acetonitrile. Stir at 600rpm for 12 hours at 60℃ until the mixture is homogeneous and free of particles.
[0099] (2) Pour the mixed solution into a polytetrafluoroethylene mold, and let it stand in a glove box for 12 hours to air dry naturally to obtain a uniformly thick electrolyte film CPE (e.g. Figure 2 (c) is shown.
[0100] The resulting product was used as a solid electrolyte membrane, a lithium metal sheet as the negative electrode, and an S@KB electrode sheet as the positive electrode. These were assembled into a CR2032 type coin-type solid lithium-ion battery, denoted as 6, in an argon-filled glove box. # Battery.
[0101] The S@KB composite cathode material was prepared using a two-step calcination method. First, 365 mg of sulfur powder and 150 mg of Ketjen Black (KB) were accurately weighed and placed in a mortar, then ground thoroughly for 1 hour. Next, the mixture was transferred to a clean, dried glass bottle and sealed with high-temperature aluminum tape. Under argon protection, the sample was placed in a tube furnace at 2 °C / min. -1The temperature was increased to 155°C at a rate of [missing information] and held for 5 hours, then allowed to cool naturally to room temperature. After cooling, the sample was ground again for 30 minutes, resealed, and placed in a tube furnace for a second calcination. The calcination was still carried out under an argon atmosphere at a rate of 2°C / min. -1 The temperature was raised to 200℃ at a constant rate, held for 2 hours, and then allowed to cool naturally. Finally, the sample was removed and ground for 30 minutes to obtain the S@KB composite cathode material. A binder was prepared in a glove box filled with an inert atmosphere. First, 11.4 g of DMF solvent was added to a glass bottle, followed by 0.44 g of PEO and 0.16 g of LiTFSI. The mixture was placed on a heated stirrer and stirred continuously at 600 rpm for 12 hours at 60℃. After stirring, the solution was allowed to stand at room temperature for 30 minutes to obtain a homogeneous binder solution. S@KB and binder were weighed according to a solid content ratio of 7:3 (active material to binder) and placed in a small beaker, with an appropriate amount of DMF solvent added. The mixture was stirred continuously at 34℃ for 10 hours until a homogeneous, particle-free viscous slurry was formed. The slurry was then evenly coated onto the surface of carbon-coated aluminum foil and placed in a vacuum drying oven at 60℃ for 12 hours. Finally, the dried electrode was cut into circular electrode sheets for subsequent battery assembly.
[0102] 6 # The battery was charged and discharged at 60℃ within a potential range of 1.5V-2.8V at different rates. When 6... # The battery exhibits a discharge specific capacity of 928.3 mAh·g at discharge rates of 0.3C, 0.5C, 1C, 2C, and 5C. -1 680.73mAh·g -1 420.71mAh·g -1 248.92mAh·g -1 and 126.68mAh·g -1 (like Figure 3 (d) shows that the initial discharge specific capacity of the CPE electrolyte is significantly lower than that of the CPE-MOF electrolyte in Examples 1-3. During charge-discharge cycle testing at 0.5C, due to incomplete reaction in the first cycle, the initial discharge specific capacity of the CPE electrolyte was 509.94 mAh·g, starting from the second cycle. -1 (like Figure 4 (d) shows that the conductivity is significantly lower than that of the CPE-MOF electrolyte in Examples 1-3. This electrolyte has an ionic conductivity of 4.17 × 10⁻⁶ at 60 °C. -4 S·cm -1 (like Figure 5 (d) shows that the ion transport number is 0.103 (as shown in the figure). Figure 6 (d) shows that the electrolyte is lower than that in Examples 1-3 (as shown in example d).
Claims
1. A method for preparing a composite solid-state electrolyte for an all-solid-state lithium-sulfur battery, characterized by, A composite polymer electrolyte film CPE is prepared by using polyethylene oxide PEO as a base and adding inorganic fillers, and a composite solid-state electrolyte CPE-MOF is prepared by adding metal-organic framework MOF-5 particles to the electrolyte film, The method comprises the following steps: Preparation of MOF-5 particles: S1. Polyvinylpyrrolidone PVP, terephthalic acid TPA and triethylamine TEA are dissolved in a solvent, and after stirring until the reagents are uniformly mixed, a solution A is obtained; S2. Zn(NO3)2·6H2O is dissolved in DMF to obtain a solution B; S3. Solution B is added to solution A, and the reaction is carried out under oil bath and stirring conditions, and the obtained white solution is cooled and precipitated, and after centrifugal washing and vacuum drying, white MOF-5 powder is obtained; Preparation of a composite solid-state electrolyte CPE-MOF: A1. Inorganic materials, lithium bis-trifluoromethanesulfonimide LiTFSI, PEO and MOF-5 are added to acetonitrile, and constant-temperature stirring is carried out until a particle-free viscous liquid is obtained; A2. The liquid is poured into a mold, and after standing and natural air drying, an electrolyte film CPE-MOF with uniform thickness is obtained; The preparation of the composite solid-state electrolyte is carried out in an argon atmosphere.
2. The method of claim 1, wherein the method is characterized by: In S1, the ratio of PVP, TPA and TEA is 6g:1.4g:300μL; The solvent is a solution obtained by mixing DMF and anhydrous ethanol in a volume ratio of 60:27; The stirring speed is 750rpm.
3. The method of claim 1, wherein the method is characterized by: In S2, the mass-volume ratio of Zn(NO3)2·6H2O to DMF is Zn(NO3)2·6H2O:DMF=267g:900mL.
4. The method of claim 1, wherein the method is characterized by: In S3, the oil bath temperature is 120℃, the stirring speed is 500rpm-650rpm, and the reaction time is 2h-4h; In the centrifugal washing process, methanol is used for washing at least 3 times to remove impurities; The vacuum drying conditions are 60℃ vacuum drying for 12h-16h.
5. The method of claim 1, wherein the method is characterized by: The MOF-5 is a three-dimensional material with Zn 2+ as the metal center and terephthalic acid TPA as the organic ligand.
6. The method of claim 1, wherein the method is characterized by: In A1, the inorganic filler includes Li 1.5 Al 0.5 Ge 1.5 (PO4)3and Li 10 GeP2S 12 , respectively denoted LAGP and LGPS; The LAGP addition amount is 5wt%-15wt%, and the LGPS addition amount is 5wt%-15wt%.
7. The method of claim 6, wherein the method is characterized by: The mass ratio of LiTFSI to PEO addition amount is 7:192, and the MOF-5 addition amount is 1wt%-5wt%.
8. The method of claim 1, wherein the method is characterized by: In A1, the constant-temperature stirring conditions are stirring at a speed of 600rpm-650rpm for at least 12h at 60℃.
9. The method of claim 1, wherein the method is characterized by: In A2, the standing time is at least 12h.
10. Application of the composite solid-state electrolyte prepared by the method of any one of claims 1-9 in a full-solid-state lithium-sulfur battery.
Citation Information
Cited By
Preparation method and application of solid-state battery three-dimensional open structure composite sulfur positive electrode material
CN122494561A